2010
DOI: 10.1111/j.1745-3933.2010.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Thin discs, thick dwarfs and the effects of stellar feedback

Abstract: We investigate the role of stellar mass in shaping the intrinsic thickness of galaxy discs by determining the probability distribution of apparent axis ratios (b/a) for two different samples that probe the faint end of the galaxy luminosity function. We find that the b/a distribution has a characteristic 'U-shape' and identify a limiting mass M_* ~ 2x10^9 M_sun below which low-mass galaxies start to be systematically thicker. This tendency holds for very faint (M_B ~ -8) dwarfs in the Local Volume, which are e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
76
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 48 publications
20
76
0
Order By: Relevance
“…This is in concordance with observations (Yoachim & Dalcanton 2006;Sánchez-Janssen et al 2010) and also expected since gas cooling is less efficient in smaller halos (Kaufmann et al 2007;Robertson & Kravtsov 2008). We explore two different scale lengths of the gaseous disk in comparison to the stellar disk, namely R g = R d , and R g = 2R d .…”
Section: Main (Disky Dwarf) Galaxiessupporting
confidence: 72%
“…This is in concordance with observations (Yoachim & Dalcanton 2006;Sánchez-Janssen et al 2010) and also expected since gas cooling is less efficient in smaller halos (Kaufmann et al 2007;Robertson & Kravtsov 2008). We explore two different scale lengths of the gaseous disk in comparison to the stellar disk, namely R g = R d , and R g = 2R d .…”
Section: Main (Disky Dwarf) Galaxiessupporting
confidence: 72%
“…Under the assumption of an inclined disk, we can use the shape of the observed distribution of RGB stars to constrain the possible inclination angle of Sag DIG. As a low mass system, several observational studies have shown that we do not expect the stars to be in a thin disk akin to large galaxies (see Roychowdhury et al 2010;Sánchez-Janssen et al 2010). From a theoretical perspective, we expect pressure support to be more important in low mass dark matter halos, leading to puffier disks (Kaufmann et al 2007).…”
Section: On the Content And Structure Of Sag Digmentioning
confidence: 99%
“…Mastropietro et al 2005;Smith et al 2010;Bialas et al 2015). The cool, thin disks of previous studies are often so thin that they have no known observable counterpart (Sánchez-Janssen et al 2010). Harassment simulations that start with cool, thin dwarf disks demonstrate that to convert the thin disks into thick disks requires sufficent tidal heating that there is additional tidal stripping of the stars (e.g.…”
Section: The Stellar Distributionmentioning
confidence: 99%